2019
DOI: 10.24263/2304-974x-2019-8-1-14
|View full text |Cite
|
Sign up to set email alerts
|

Method of thermometric determination of thermophysical characteristics of thermolabs materials

Abstract: Introduction. The analytical researches of methods and devices of determination of thermophysical properties of complicated structure and chemical composition of products of processing industry are carried out in order to increase the accuracy of measurements. Materials and methods. The basis of the studied devices is thermoelectric converters of temperature and heat flow in the form of "auxiliary wall". To improve the accuracy of the measurements of the thermophysical characteristics of materials, the graph-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The mechanism of probiotics' biological action in ruminants has only been partially elucidated, but recent research has shown that it is complex and multifaceted. It is established that the metabolic effect of probiotics in the digestive tract of ruminants largely depends on the quantitative and qualitative composition of microorganisms and technology of probiotic preparations [Bondarenko 2010, Polishchuk and Bulavkina 2010, Mazurenko 2011, Reshetnichenko et al 2012, Kyldiyarova 2016. It has been experimentally proven that the use of probiotics in the diet of ruminants enhances the barrier functions of in-testinal mucosal cells by activating the processes of cytoskeletons' phosphorylation of their protein structures and stimulates secretion of mucus and chlorides [Caramia 2004, Krysenko et al 2010.…”
Section: Characteristics Classification and Mechanism Of Biological A...mentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanism of probiotics' biological action in ruminants has only been partially elucidated, but recent research has shown that it is complex and multifaceted. It is established that the metabolic effect of probiotics in the digestive tract of ruminants largely depends on the quantitative and qualitative composition of microorganisms and technology of probiotic preparations [Bondarenko 2010, Polishchuk and Bulavkina 2010, Mazurenko 2011, Reshetnichenko et al 2012, Kyldiyarova 2016. It has been experimentally proven that the use of probiotics in the diet of ruminants enhances the barrier functions of in-testinal mucosal cells by activating the processes of cytoskeletons' phosphorylation of their protein structures and stimulates secretion of mucus and chlorides [Caramia 2004, Krysenko et al 2010.…”
Section: Characteristics Classification and Mechanism Of Biological A...mentioning
confidence: 99%
“…Probiotics also have a detoxifying effect on compounds formed in the host under the influence of pathogens [Charalampopoulos and Rastall 2009, Kolisnik et al 2010, Kotsumbas et al 2013, Kordon 2014. Probiotic preparations, in contrast to antibiotics, which inhibit immune functions in the body, stimulate the synthesis of antibodies against pathogens [Mazurenko 2011].…”
Section: Characteristics Classification and Mechanism Of Biological A...mentioning
confidence: 99%
See 3 more Smart Citations